The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2304/plat.2007.6.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Learning about the Means to the End: What US Introductory Psychology Students Report about Experimental Participation

Abstract: Previous research has shown that when asked to rate their agreement with statements regarding their attitudes towards participation in psychological experiments, students reported that their participation was of educational value (e.g., Bowman and Waite, 2003; Landrum and Chastain, 1995). We investigated what kinds of learning experiences students would report when prompted with open ended questions regarding their participation. Four open ended questions asked how seriously participants took the research expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Mandatory research participation is a common component in undergraduate psychology research programs, primarily justified on the basis of enhancing student experience by promoting insight into research methods, processes, and findings (Chin & Gibbs Stayte, 2015; Darling et al, 2007; Landrum & Chastain, 1995; Moyer & Franklin, 2011; VanWormer et al, 2014). Although there is a growing body of literature surrounding why student choose to engage (or not) with research in general (Bowman & Waite, 2003; Elicker et al, 2010; Rocchi et al, 2016), previous research has not examined how choices are made to select specific studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandatory research participation is a common component in undergraduate psychology research programs, primarily justified on the basis of enhancing student experience by promoting insight into research methods, processes, and findings (Chin & Gibbs Stayte, 2015; Darling et al, 2007; Landrum & Chastain, 1995; Moyer & Franklin, 2011; VanWormer et al, 2014). Although there is a growing body of literature surrounding why student choose to engage (or not) with research in general (Bowman & Waite, 2003; Elicker et al, 2010; Rocchi et al, 2016), previous research has not examined how choices are made to select specific studies.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have measured actual learning have found that research participation increases knowledge to a similar extent as lecture attendance (Elliott, Rice, Trafimow, Madson, & Hipshur, 2010) and is especially beneficial for increasing understanding of research procedures, research ethics, and the diversity of psychology as a discipline (Bowman & Waite, 2003; Rosell et al, 2005). Participating in research has also been associated with self-perceived increases in understanding of the specific experimental topic (Darling, Goedert, Ceynar, Shore, & Anderson, 2007; Moyer & Franklin, 2011), psychology more generally (Chin & Gibbs Stayte, 2015; Landrum & Chastain, 1995), and research methods and processes (Chin & Gibbs Stayte, 2015; Darling et al, 2007; VanWormer et al, 2014). Perceived benefits appear to be slightly lower if research participation is mandatory compared with when it is voluntary (Nimmer & Handelsman, 1992; Roberts & Allen, 2013).…”
mentioning
confidence: 99%
“…Previous research has consistently shown that undergraduate students perceive their experience of participating in psychological studies as educational, positive, and beneficial to them (Bowman & Waite, 2003; Darling et al, 2007; Elliot et al, 2010; Landrum & Chastain, 1995; Rosell et al, 2005; VanWormer et al, 2014). For example, VanWormer and colleagues (2014) found that undergraduate students reported increased understanding of, and interest in, research after participating in studies.…”
Section: Undergraduate Students’ Perceptions Of Participating In Psycmentioning
confidence: 99%
“…A study by Darling and colleagues (2007) provides some suggestion that students might learn about more than just the process of research from participating in research studies. In response to open-ended questions, they asked undergraduate students to write about what they gained from participating in studies.…”
Section: Undergraduate Students’ Perceptions Of Participating In Psycmentioning
confidence: 99%
“…Those first year students who participated in research reported an increment understanding psychological research procedures as well as an increment understanding contemporary psychology. Although the methods used have usually been based in self-reports, some researchers have investigated if the students get any type of learning benefit after their participation in a certain research (Darling et al, 2007;Rosell et al, 2005). One of the most common results found is that students usually report that they learn not only about psychological content but also about the process of conducting psychological research (Darling et al, 2007).…”
Section: Research Participation Improves Student's Exam Performancementioning
confidence: 99%